Does the science of Theoretical Mysticism exist? - Muhammad Fanaei Eshkvari (حکمت اسرا, 2011)
The possibility of theoretical mysticism depends on a few paradigms: a) the possibility of direct mystical knowledge b) this kind of knowledge’s being credibly able to find the realities c) Man is capable of having direct and intuitional knowledge d) we accept that personal intuitional knowledge can be conveyed to others. After showing how the above paradigms have been rejected by different mystical and philosophical schools in the East and the West, the author attempts to demonstrate that theoretical mysticism’s being possible depends on resolving the above four paradigms. With a comparative approach the paper also discusses the case of mystical philosophy and whether it is credible.